Importance of complement system components in ovarian endometriomas. A comparative cohort study - Anna V. Chizhova; Elena V. Kudryavtseva; Larisa G. Polushina; Maksim A. Kopenkin (Гинекология)
Background. Ovarian endometriomas are one of the most common ovarian neoplasms. There are specific ultrasound criteria for this type of endometriosis; however, in some cases, differential diagnosis from other ovarian tumors is challenging.